179k views
2 votes
Letℎ()h(x)be the inverse of()f(x). Ifℎ()=−4+1h(x)=−4x+1, which of the following represents()f(x)?

Letℎ()h(x)be the inverse of()f(x). Ifℎ()=−4+1h(x)=−4x+1, which of the following represents-example-1
Letℎ()h(x)be the inverse of()f(x). Ifℎ()=−4+1h(x)=−4x+1, which of the following represents-example-1
Letℎ()h(x)be the inverse of()f(x). Ifℎ()=−4+1h(x)=−4x+1, which of the following represents-example-2
User Moien
by
6.0k points

1 Answer

4 votes

In order to find f(x), we need to calculate the inverse of h(x)


h(x)=-4x+1

y=h(x)


y=-4x+1

We substitute x with y and y with x


x=-4y+1

Then we isolate the y


4y=-x+1
y=-(1)/(4)x+(1)/(4)

ANSWER

f(x) is


f(x)=-(1)/(4)x+(1)/(4)

The correct choice is the first one

User Saurabh Bhandari
by
5.9k points